O BRASIL E O MERCOSUL: ATORES DOMÉSTICOS E OSCILAÇÕES DA POLÍTICA EXTERNA NOS ÚLTIMOS 30 ANOS - Mariano, Marcelo Passini [UNESP]; Ramanzini, Haroldo; Vigevani, Tullo [UNESP] (CEDEC, 2021)
The purpose of this article is to analyze the role of Mercosur for Brazilian foreign policy from 1991 to 2021. We will argue that there is a path of gradual loss of centrality by the bloc for Brazilian foreign policy and a reduction in the levels of trade. Thus, the decline in the bloc’s priority for Brazil, observed in Temer and Bolsonaro administrations, cannot be examined without referencing difficulties that had already manifested in previous governments, in fact since 1995, although with different characteristics. During these thirty years, Brazilian business and political elites have not maintained the same interest in integration. Likewise, the transformations of the international system and the evolution that they produced in the perception of the elites regarding the role that Brazil should play in the world were not absorbed as systemic incentives for the deepening of regional integration. The bloc celebrates its 30th anniversary demonstrating an important resilience, despite the context of lesser engagement of the countries, the accumulated effects of successive political and trade crises and the diminishing economic importance in relation to other extra-bloc partners, factors that raise important questions in relation to its future.

O objetivo deste artigo é analisar o Mercosul na política externa brasileira no período de 1991 a 2021. Argumentaremos que há uma trajetória de gradual perda de centralidade do bloco para a política externa brasileira e de redução nos níveis de intercâmbio comercial. Assim, o declínio da prioridade do bloco para o Brasil, observado nos governos Temer e Bolsonaro, não pode ser considerado fato desenraizado de problemas que já se manifestavam nos governos anteriores, em verdade desde 1995, ainda que com diferentes características. Nestes trinta anos, as elites empresariais e políticas brasileiras não mantiveram o mesmo interesse pela integração. Do mesmo modo, as transformações do sistema internacional e a evolução que produziram na percepção das elites a respeito do papel que o Brasil deveria desempenhar no mundo não foram absorvidas como incentivos sistêmicos para o aprofundamento da integração regional. O bloco completa trinta anos demonstrando importante resiliência, apesar do contexto de menor engajamento dos países, dos efeitos acumulados das sucessivas crises políticas e comerciais e da diminuição da importância econômica em relação a outros parceiros extrabloco, fatores que colocam importantes interrogações em relação ao seu futuro.
BRAZIL AND MERCOSUR: DOMESTIC ACTORS AND FOREIGN POLICY FLUCTUATIONS IN THE LAST 30 YEARS
Keywords: Brazilian Foreign Policy; Mercosur; Regional Integration; Política Externa Brasileira; Mercosul; Integração Regional